Strengthening Character of Environment Preservation Using Wayang Story Lakon Dewa Ruci: an Ecological Literature Analysis - Djoko Sulaksono; Kundharu Saddhono (Universitas Negeri Surabaya, 2018)
Wayang is one of art which sourced from Javanese culture. Wayang for Javanese society have a function not only being an entertainment, but also being guidance ways. Wayang as guidance because on wayang story contain some of character values sourced from Javanese culture which especially dedicated for Javanese society. This research is qualitative descriptive using ecological literature approach. Focus on this research are to describe and explain about ways to strengthening characters of environment preservation using wayang story Lakon Dewa Ruci. Data resourced is wayang text lakon Dewa Ruci and some informants from dalang. Data collected technique using study literature and in-depth interview. Some data which founded then analyzed by using interactive technique, which the phase are data reduction, data display, and conclusion drawing. Triangulation technique using for data validity. Result of the research can be find in Lakon Dewa Ruci there are representation of teach how to preserve the environment. One of them can be seen when Bima looking for Tirta Perwita Sari, he must fused with nature, he must plunging into ocean. Therefore, characters of environment preservation also can be seen on Bimas journey when looking ngelmu sejati until he meet Dewa Ruci. Keywords: character of environment preservation, wayang story, Lakon Dewa Ruci, ecological literature.